An experimental study of defrost on treated surfaces: Effect of frost slumping. (April 2018) - Liu, Y.; Kulacki, F.A.
Highlights: Defrost processes are different on surfaces with varying wetting properties. Frost falls off as a rigid body on the surperhydrophobic surface. Frost melts, and part of the frost falls off with the draining meltwater on the superhydrophilic and plain surfaces. Meltwater motions are suggested as a key factor of the defrost behaviors. Frost slumping generally reduces defrost time and improves defrost efficiency. Abstract: Experiments of defrost processes are reported for superhydrophilic, plain and superhydrophobic surfaces which are vertically placed. On the superhydrophobic surface, the frost layer falls off as a rigid body. On the superhydrophilic and plain surfaces, the frost melts, and part of the frost layer falls off with the draining meltwater. Defrost time is thus less for the superhydrophobic surface compared to that for superhydrophilic and plain surfaces. Frost slumping conditions are analyzed with a static force balance, and criteria for frost release are presented. Meltwater motions are suggested as the key factor of the defrost mechanism. When the volume flux of meltwater in the frost is greater than the melting rate, the meltwater is absorbed into the frost. When the volume flux of meltwater is less than the melting rate, it accumulates and drains on the surface. Water accumulation favors frost slumping because the adhesive force becomes weak. Frost slumping generally shortens defrost time and improves defrost efficiency based on our measurements.